Lichen Planus in Down Syndrome: Treatment with Systemic Retinoid - an Observation - Hye, Mohammad A; Dutta, Siddhartha Shankar (Medicine Today, 2020)
Introduction: Pancreatic calculi (PC) are not an uncommon surgical condition in daily practice.Alcohol, smoking, genetic factors, metabolic disturbances and defects in immunity are some of the known etiological agents. The common presentations are severe abdominal pain, vomiting, malabsorbtion, weight loss, diabetes mellitus etc. Case Report: We have managed ten cases in our hospital,Initial medical treatment was given to all of the patients, followed by open surgical procedure. Discussion: Endoscopic stone removal is the best procedure in a higher center. Open surgical procedure is needed in some cases. Conclusion: We have done ten cases of open pancreatolithotomy in our district hospital. The outcome of the procedure is satisfactory. Medicine Today 2020 Vol.32(1): 73-75